INFORMAL ENGLISH LEARNING WITH ONLINE DIGITAL TOOLS: NON-LINGUIST STUDENTS - Oksana Yurieva; Tetiana Musiichuk; Dina Baisan (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The internet has offered numerous opportunities for educational content delivery. The main current delivery models for learning a language online range from more formal structured approaches provided by schools and universities, which typically take place in a VLE (Virtual Learning Environment) or LMS (Learning Management System), to more informal unstructured approaches, including Virtual Worlds like Second Life and MMORPGs (Massively Multiplayer Online Role-Playing Games) like World of Warcraft. The purpose of this study is to analyse the experiences and perceptions of the online digital tools that provide engagement with the English language outside the classroom by the non-linguist students at a Ukrainian public university. The study is based on the quantitative and qualitative data collected employing an online questionnaire including Likert-type ratings, multiple-choice questions, and free-text responses to open questions. The questionnaire inquires about students' experiences with 17 technologies not related to their classroom activities, how frequently they are used, how helpful the students find them for their language acquisition in general, and how useful they are considered for the development of particular language competencies (writing, reading, speaking, listening, pronunciation, grammar, communicative competence). The results of the survey attest to regular students' engagement with the English language involving online technologies, which leads to implications for foreign language learners, teachers, and researchers of second language acquisition for incorporating online digital tools for foreign language acquisition beyond the classroom. Being aware of how students engage with technology outside the classroom may facilitate educators in increasing learners' engagement with the foreign language, provide additional practice, and produce an emotional response, which increases retention of information.